Polyaniline-modified porous carbon tube bundles composite for high-performance asymmetric supercapacitors. (1st December 2018) - Zhao, Jing; Li, Yiju; Chen, Xi; Zhang, Hongquan; Song, Congying; Liu, Zheng; Zhu, Kai; Cheng, Kui; Ye, Ke; Yan, Jun; Cao, Dianxue; Wang, Guiling; et al.
Abstract: In this work, activated carbon tube bundles (ACTBs) with porous hollow structure are prepared using dandelion fluffs as precursors. The open-framework porous structure of the ACTBs contributes to large specific surface area and enhanced electrochemical performances. Then the ACTBs are further modified with polyaniline (PANI) using the in-situ polymerization method, the unique hollow tube structure of the ACTBs effectively increases the growth area for the PANI. The PANI modified ACTBs (PANI/ACTBs) composite exhibits an excellent rate performance due to the highly retained porous hollow tube structure, which promotes the electrolyte ions diffusion and electron transport. Meanwhile, the ACTBs and PANI/ACTBs serve as the cathode and anode electrode materials for asymmetric supercapacitor, respectively. As a result, the asymmetric supercapacitor displays a high energy density of 42 Wh kg −1 and a capable cycling stability. These results demonstrate that the PANI/ACTBs composite is a promising electrode material for the energy storage devices. Graphical abstract: Highlights: The porous structure of the ACTBs contributes to the enhancement of the specific surface area and cycling stability. The ACTBs can solve the aggregation problem and provide more space for the volume changes of the PANI particles. The PANI/ACTBs exhibits high capacitance and the good cycling stability due to the combined advantages of PANI and ACTBs. The PANI/ACTBs composite exhibits high energy density of 42 Wh kg −1 .